3x(4-x)=6

Simple and best practice solution for 3x(4-x)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(4-x)=6 equation:



3x(4-x)=6
We move all terms to the left:
3x(4-x)-(6)=0
We add all the numbers together, and all the variables
3x(-1x+4)-6=0
We multiply parentheses
-3x^2+12x-6=0
a = -3; b = 12; c = -6;
Δ = b2-4ac
Δ = 122-4·(-3)·(-6)
Δ = 72
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{72}=\sqrt{36*2}=\sqrt{36}*\sqrt{2}=6\sqrt{2}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(12)-6\sqrt{2}}{2*-3}=\frac{-12-6\sqrt{2}}{-6} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(12)+6\sqrt{2}}{2*-3}=\frac{-12+6\sqrt{2}}{-6} $

See similar equations:

| 2y+17=314 | | 8p+9=13 | | x8+9=21 | | 2v-7=20 | | 9−c=−12 | | 3p+9=13+7p | | 4x-5=4(x-12)+7 | | 7(u+2)=9u+12 | | 5(x-3=2x+15 | | 9x+0.4=45.4 | | 89=−5d+9 | | 10=4r−10 | | -34=9(8y-9) | | 10+t=t | | 14x+18=3x-8 | | 7(p-2)=56 | | −x2=7−8x | | 4y−2=26 | | 75+50=x | | x+x+8+90=180 | | 1/2x-6+2/3x=7/6x+8 | | 2.25x-2.84=8.94 | | 95−63=60-x | | 6x+120=90 | | 6x+20=90 | | 8x-15=-6+8x7x-2 | | 3x-5=12+x | | 3w+3w-6+4w+3w=14 | | 5y+13=6y-8 | | -4(3t-4)+7t=2t-3 | | -4b2+40b-96=0 | | x+12=1+4x |

Equations solver categories